The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1111/j.1349-7006.2000.tb00964.x
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Inactivation with Acridine Orange on a Multidrug‐resistant Mouse Osteosarcoma Cell Line

Abstract: Overcoming multidrug resistance (MDR) is an urgent issue to improve the prognosis of osteosarcoma patients. In this study, we undertook to clarify the effect of photodynamic therapy (PDT) with acridine orange (AO) on the MDR mouse osteosarcoma (MOS/ADR1) cell line, by comparing the outcome with the effect on a chemosensitive osteosarcoma (MOS) cell line. Cultured cells of MOS and MOS/ADR1 cell lines were exposed to AO at various concentrations for various times, followed by long-or short-term (10 or 1 min) ill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 27 publications
1
59
0
1
Order By: Relevance
“…[15][16][17][18][19] Milla et al showed that PDT-resistant squamous carcinoma cells had a more¯broblastic morphology, higher number of stress¯bers, more expression of cell-substrate adhesion proteins and higher expression of phospho-survivin but few di®erences in intracellular PpIX content after incubation with ALA methyl derivative. 20 Topical ALA PDT has been successfully used for some resistant cases of cutaneous T-cell lymphoma.…”
Section: Interaction Of Mdr and Psmentioning
confidence: 99%
“…[15][16][17][18][19] Milla et al showed that PDT-resistant squamous carcinoma cells had a more¯broblastic morphology, higher number of stress¯bers, more expression of cell-substrate adhesion proteins and higher expression of phospho-survivin but few di®erences in intracellular PpIX content after incubation with ALA methyl derivative. 20 Topical ALA PDT has been successfully used for some resistant cases of cutaneous T-cell lymphoma.…”
Section: Interaction Of Mdr and Psmentioning
confidence: 99%
“…Consequently, this in vivo study was conducted. Previously, we reported that the intraperitoneal administration of AO at 10 mg/ kg followed by blue light excitation inhibited the tumor growth of osteosarcoma developing from a different cell line (MOS) than LM8 in vivo (14,15,18,19). Recently, we also found that the intravenous administration of AO at 1.0 mg/kg is useful for PDD of mouse osteosarcomas in nude mice.…”
Section: Discussionmentioning
confidence: 85%
“…AO was used at a concentration of 1.0 mg/kg, since previous studies showed that this concentration yields the strongest cytocidal effect and lowest toxicity in mice (10). The illumination time (10 min) and time-point of illumination (2 h after AO injection) were also selected based on the results of previous studies (9,10,14,15).…”
Section: Methodsmentioning
confidence: 99%
“…Activated oxygen (singlet oxygen) oxidizes the fatty acids of the lysosomal membranes, resulting in leakage of various lysosomal enzymes, such as proteases, lipases, and nucleases, into the cytosolic space. It has been reported that singlet oxygen scavengers, like L-histidine, inhibited the cytocidal effect of AO-PDT [19,36].…”
Section: Ao-pdt and Ao-rdtmentioning
confidence: 99%
“…We also demonstrated that AO exerts selective cytocidal effects against sarcoma cells both in vitro and in vivo after illumination with visible light or irradiation of low-dose X-rays. It is available clinically for photodynamic therapy (PDT) [16][17][18][19][20][21] or radiodynamic therapy (RDT) [22][23].…”
Section: Introductionmentioning
confidence: 99%